Piezoelectric property degradation and cracking impacts on the lifetime performance of energy harvesters. (July 2021) - Salazar, R.; Larkin, K.; Abdelkefi, A.
Highlights: Property lifetime variations that can impact a damaged energy harvester are investigated. Importance of operating frequency range and load resistance is described during the degradation. Combinations of cracking and piezoelectric degradation cause a wide shift in the system. It is found that energy harvesters are very sensitive to changes in optimal load resistance. This investigation gives further understanding of fatigue and push this technology forward. Abstract: The development of cantilever-based piezoelectric vibrational energy harvesters (VEHs) is reaching a critical transition into commercial applications but is being held back because of the lack of understanding regarding the fatigue of these systems. Identifying possible fatigue phenomena for piezoelectric VEH gives a good basis of knowledge for the creation of numerical fatigue models. The development of an electromechanical model is carried out to capture the property variations that can impact a damaged cantilever VEH. The influence of damage from crack and decreased piezoelectric performance that can occur during the lifetime of VEH is investigated. The importance of the operating frequency range and optimum load resistance is described for a wide range of stiffness reduction due to cracking and piezoelectric property degradation. Cracks are the most general form of fatigue and impact the natural frequency of the system the most. Piezoelectric property degradation affects the electrical properties and performance of the patch. Combinations of cracking and piezoelectric property degradation cause a wide variety of shift in the system. It is found that these energy harvesters are very sensitive to changes in load resistance as they degrade which can influence the coupled frequency response. The identification of how these systems degrade gives future researchers the knowledge they need to pursue further understanding of fatigue and push this technology forward.